Klotho protein, albumin level, left ventricular and left atrium dimensions are independently associated with moderate and severe cardiac allograft vasculopathy in heart transplant recipients. (25th November 2020) - Szczurek, W; Gasior, M; Skrzypek, M; Romuk, E; Zembala, M; Szygula Jurkiewicz, B
Abstract: Background: Cardiac allograft vasculopathy (CAV) is one of the main risk factors influencing graft loss and patients survival. An important element of monitoring the patient after heart transplantation (HT) is the assessment of non-invasive indicators associated with the occurrence and progression of CAV. Therefore, new noninvasive sensitive and specific tools are necessary for detecting CAV early, which may result in the modification of immunosuppressive therapy, increase in statin doses, and intensive treatment of CAV-related comorbidities. Purpose: The aim of the study was to research for factors associated with occurrence of moderate to severe CAV in heart transplant recipients. Methods: Our analysis included consecutive adult patients after HT with CAV who underwent routine visits in our institution between 2015–2017. Exclusion criteria included history of kidney diseases, hepatitis B and C, autoimmune diseases, chronic pancreatitis or thyroid diseases, and cerebrovascular accidents. During each visit, all patients underwent echocardiography, laboratory tests, immunosuppressive drugs serum concentration analyses, and coronary angiographies. In addition, Klotho protein concentration was measured in all patients using sandwich enzyme-linked immunosorbent assay (ELISA) with the commercially available kit. Coronary angiographies of all patients enrolled to the study were reviewed by two independent interventional cardiologists to accurately classify coronary artery lesions according to International Society for Heart and Lung Transplantation (ISHLT) guidelines. Then, patients were divided into a group with mild CAV (1) and moderate to severe CAV (2/3). The local institutional review board of the Medical University of Silesia approved the study protocol, and all patients provided informed consent. Results: The final group consisted of 141 patients with CAV. The age of the patients was 60.0 (53.0–66.0) and 77.5% of them were male. The median time from HT to include in the study was 11.6 (8.5–15.0) years. The frequency of CAV 2/3 in the analysed population was 36.6%. All included patients received optimal immunosuppressive therapy consisting of a calcineurin inhibitor (tacrolimus or cyclosporin) and mycophenolate mofetil. Multivariate analysis of logistic regression showed that Klotho protein (OR = 0.719 [0.598–0.866], p<0.001), albumin (OR=0.790 [0.686–0.910] p<0.001), left ventricular diastolic dimension (OR =1.135 [1.054–1.222], p<0.001), and left atrium dimension (OR=1.058 [1.013–1.106] p=0.012) were independent factors of CAV 2/3 presence. Conclusions: Lower Klotho and albumin levels, as well as left ventricular and left atrium dimensions are the independent factors of moderate to severe CAV presence. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): MEdical University of Silesia, Katowice, Poland